In Vitro Antidiabetic Activities of Extract and Isolated Flavonoid Compounds from Artocarpus altilis (Parkinson) Fosberg - Puspa Dewi Narrij Lotulung; Tjandrawati Mozef; Chandra Risdian; Akhmad Darmawan (Universitas Gadjah Mada, 2014)
The antidiabetic activity test through a mechanism of inhibition of α-glucosidase enzyme was studied against ethanol, n-hexane, ethyl acetate and n-butanol fractions of ethanol extract of Artocarpus altilis (Parkinson) Fosberg (Moraceae) leaves and four flavonoid compounds isolated from ethyl acetate extracts of A. altilis. Ethyl acetate fraction has strongest antidiabetic activity compared to ethanol, n-hexane, and n-butanol fractions with IC50values5.98,6.79, 440.18and14.42μg/mL, respectively. Four flavonoid compounds (1-(2,4-dihydroxyphenyl)-3-[8-hydroxy-2-methyl-2-(4-methyl-3-pentenyl)-2H-1-benzopyran-5-yl]-1-propanone (AC-31), 2-geranyl-2',3,4,4'-tetrahydroxy dihydrochalcone (AC-51), 8-geranyl-4',5,7-trihydroxyflavone (AC-33) andcyclocommunol (AA-3), have been isolated from ethylacetate fraction. AC-31 was the strongest antidiabetic compound compared to AC-51, AC-33 and cyclocommunolwithIC50values are 15.73, 24.41,49.49,and72.20μg/mL. Kineticstudies of AC-31 using Lineweaver-Burk method showed that inhibition mechanism of enzymeα-glucosidase was anon-competitivetype.